Electronic Arbitration as a Means of Settling Disputes in E-commerce Contracts - Mahdi, Ridda (Journal of Legal Studies and Researches, 2022)
Introducing modern means of communication, into the field of commerce, resulted in what is known as electronic commerce. The latter has many problems, especially with regard to means of settlement. This development has been embodied in the means of settlement through alternative means that are carried out via the Internet, including electronic arbitration.